Challenges and perspectives in obstructive sleep apnoea: Report by an ad hoc working group of the Sleep Disordered Breathing Group of the European Respiratory Society and the European Sleep Research Society. Issue 3 (16th September 2018) - Randerath, Winfried; Bassetti, Claudio L.; Bonsignore, Maria R.; Farre, Ramon; Ferini-Strambi, Luigi; Grote, Ludger; Hedner, Jan; Kohler, Malcolm; Martinez-Garcia, Miguel-Angel; Mihaicuta, Stefan; Montserrat, Josep; Pepin, Jean-Louis; et al.
Obstructive sleep apnoea (OSA) is a major challenge for physicians and healthcare systems throughout the world. The high prevalence and the impact on daily life of OSA oblige clinicians to offer effective and acceptable treatment options. However, recent evidence has raised questions about the benefits of positive airway pressure therapy in ameliorating comorbidities. An international expert group considered the current state of knowledge based on the most relevant publications in the previous 5 years, discussed the current challenges in the field, and proposed topics for future research on epidemiology, phenotyping, underlying mechanisms, prognostic implications and optimal treatment of patients with OSA. The group concluded that a revision to the diagnostic criteria for OSA is required to include factors that reflect different clinical and pathophysiological phenotypes and relevant comorbidities ( e.g. nondipping nocturnal blood pressure). Furthermore, current severity thresholds require revision to reflect factors such as the disparity in the apnoea–hypopnoea index (AHI) between polysomnography and sleep studies that do not include sleep stage measurements, in addition to the poor correlation between AHI and daytime symptoms such as sleepiness. Management decisions should be linked to the underlying phenotype and consider outcomes beyond AHI. Clinical and pathophysiological phenotyping and personalised diagnostic and therapeutic procedures remain challenges in obstructive sleep apnoea management http://ow.ly/OhNU30jOCr3